Infections in patients with multiple myeloma treated with conventional chemotherapy: a single-center, 10-year experience in Pakistan - Mohammad Faizan Zahid; Natasha Ali; Myra Nasir; Maria Haider Baig; Mustafa Iftikhar; Syed Usman Bin Mahmood; Arhama Malik; Sara Atif; Mohammad Asim Beg (Hematology, Transfusion and Cell Therapy, 2019)
Introduction: Multiple myeloma (MM) is a common hematologic malignancy with variable degrees of immunodeficiency. Disease- and treatment-related compromise of the immune system predisposes patients to infections, which are a major cause of morbidity and mortality. Objective: We aimed to establish the incidence and main characteristics of infections in MM patients treated at our center over a 10-year period. Method and results: Of the 412 patients retrospectively analyzed, 154 (37.4%) were documented to have at least one episode of infection and were included in this study. A total of 244 infectious episodes were documented. The most common site of infection was the lung, followed by the genitourinary system. The most common infections were bacterial, followed by viral. Escherichia coli were the most common organism. In 160 (65.5%) episodes, the organism was not isolated. Thalidomide with dexamethasone was the most common treatment regimen, followed by melphalan with dexamethasone. Infection was the main cause of death in 26 (6.3%) out of all 412 patients. Conclusion: Infections are a notable cause of morbidity and mortality in the clinical course of MM patients. By considering patient and disease characteristics, a risk-adapted selection of the MM treatment should be employed, with special attention toward patient age and disease-associated organ dysfunction. Patient education, access to healthcare and physician vigilance are also essential. Vaccination and antimicrobial prophylaxis may be considered prior to or during therapy. Keywords: Multiple myeloma, Infections, Infectious complications, Complication, Mortality, Treatment